Hierarchical analysis of determinants of HIV vertical transmission: a case-control study - Poliana Germano Bezerra de Sá Siqueira; Gabriella Morais Duarte Miranda; Wayner Vieira de Souza; Gerlane Alves Pontes da Silva; Antonio da Cruz Gouveia Mendes (Revista Brasileira de Saúde Materno Infantil, 2021)
Abstract Objectives: to analyze the association of socioeconomic, obstetric, pediatric and prophylactic factors to the vertical transmission of HIV in children followed at a reference service in Recife between 2010 and 2015. Methods: case-control nested the cohort of children exposed to vertical transmission of HIV. A univariate and multivariate statistical analysis was performed on the association of socioeconomic, obstetric, pediatric and prophylactic measures with the outcome. We considered two multivariate approaches, conventional and hierarchical, the latter made it possible to consider different levels of determination. Results: 46.5% of the mothers had low schooling, 69.6% without work-related wages and 35.7% received a family grant. Women with postpartum diagnosis and less than 6 prenatal appointments had a greater chance of vertical transmission. Prophylactic measures were statistically associated with prevention of transmission (p<0.1%). Conclusions: vertical risk factors for HIV transmission were identified: no sewage system, at least six prenatal consultations, first care of the child with more than two months and no prophylaxis in pregnancy and childbirth. Determining factors for which specific policies and programs exist and their non-access social determination evidence of HIV vertical transmission.